Rationale and Value of Natural History Collections Digitisation - Scoble, Malcolm (Biodiversity Informatics, 2010)
Natural science collections comprise a small component of a more extensive source of data on which questions about the natural world may be addressed. However, NHC data offer, when digitised, an exceptional resource: within collections lies the most extensive dataset that exists of the planet’s biodiversity. Indeed, our entire knowledge of most species is based on just one or very few specimens housed in natural science collections. Nevertheless, for most species, collections provide us with the best record available. The physical presence of specimens allows us to examine them many times using new techniques (e.g. the extraction and study of molecular data). In this article we argue in favor of expedited digitisation of NHC data.